Psychological modalities for the treatment of localized provoked vulvodynia: a scoping review of literature from 2010 to 2023 - Logan, Gabrielle S; Gustafson, Diana L; Swab, Michelle; Rains, Alex; Miller, Michelle E; Jackman, Victoria A; Bajzak, Krisztina (Journal of sexual medicine, 2025)
Localized provoked vulvodynia is a common sexual health condition for which there is a lack of consensus on effective management, even though it can have a significant negative impact on psychological wellbeing, sexual functioning, and quality of life for women and their partners. To map the research landscape related to the effectiveness/efficacy of psychological treatments for localized provoked vulvodynia, identify gaps, and make recommendations for future research. We used Arksey and O'Malley's approach to conducting a scoping review to identify, organize, and summarize research published between 2010 and 2023 that investigated the efficacy or effectiveness of interventions in the management of localized provoked vulvodynia. Inclusion and exclusion criteria and the search strategy were developed by subject experts in collaboration with a health sciences librarian. A PubMed search used controlled vocabulary and keyword terms relating to vulvodynia, which were then translated into other databases. Studies not published in English or French were excluded. We did not consider other subsets of vulvodynia.Articles were uploaded to Covidence, duplicates removed, and titles and abstracts screened. The remaining articles were subject to a 2-person, independent full-text review followed by a hand search of eligible articles. All intervention studies were included regardless of the study design. Study details were reported narratively and analyzed. Of the 88 included articles published between January 2010 and March 2023, 15 reported on the efficacy/effectiveness of psychological treatments for localized provoked vulvodynia, including group educational seminars, cognitive behavioral therapy, acceptance and commitment therapy, and somatocognitive therapy. Cognitive behavioral therapy was the most common form of psychological treatment studied (n = 7) with interventions for both individuals and couples. Education about the condition and the therapeutic process was a component of many interventions. Psychological therapies may be of some benefit, but only 1 RCT evaluating the efficacy of acceptance and commitment therapy appeared adequately powered to demonstrate improvement in dyspareunia. Studies sampled homogenous patient populations, primarily consisting of White, urban-dwelling, educated, partnered, heterosexual cis-women. Evidence of efficacy/effectiveness, drawn mainly from small studies, is promising and highlights opportunities for more robust studies with heterogeneous populations, more research on the role of education in treatment success, and greater attention to assessing patient-driven outcomes in partnered and unpartnered women.